Temperature-induced phase transitions of the ordered superlattice assembly of Au nanoclusters - Chaki, N. K.; Vijayamohanan, K. P. (Journal of Physical Chemistry B, 2005)
Superlattices of monolayer protected metallic and semiconducting nanoclusters have attracted significant attention due to their promising applications in nanotechnology. In this paper, we investigate the effect of temperature on the ordered superlattice structure of relatively larger sized An nanoclusters passivated with dodecanethiol [ca. Au-1415(RS)(328)] with the help of in situ temperature controlled X-ray diffraction (XRD) and infrared spectroscopy (IR) in conjunction with thermogravimetric (TG) and differential scanning calorimetric (DSC) analysis. In brief, monolayer protected Au nanoclusters (AuMPC) were prepared by a modified Brust synthesis technique, where dodecanethiol itself acts as both phase transfer and simultaneous capping agent during the reduction process, generating an average particle size of 3.72+/-0.4 nm after repeated solvent extraction and careful fractionation experiments. These particles are characterized with the help of UV-vis, transmission electron microscopic (TEM), IR, and NMR techniques, where effective capping as well as the superlattice formation on the TEM grid is evident from the combined analysis of these results. In situ low-angle XRD analysis shows that the particles undergo an irreversible phase transition in the temperature range of 100-115degreesC, which is also reflected in the data from in situ IR analysis. However, the DSC analysis does not account for this phase transition, although the reversible phase transition due to the alkyl chain dynamics is in good agreement with the previously reported results. These results indicate the formation of temperature-induced, diffusion-limited phase transition involving nonequilibrium fractal structures, which is in good agreement with the previous available theoretical studies. The determination of the temperature window for the stability of these ordered assemblies would be used to understand the effect of thermal stress for device applications.

Electrochemical organization of monolayer protected gold nanoclusters on single-walled carbon nanotubes: significantly enhanced double layer capacitance - Mahima, Subhramanyam; Chaki, N. K.; Sharma, J.; Kakade, Bhalchandra A.; Pasricha, R.; Rao, A. M.; Vijayamohanan, K. (Journal of Nanoscience and Nanotechnology, 2006)
This paper reports a novel electrochemical route for anchoring monolayer protected gold nanoclusters (size 8 +/- 0.2 nm) on single-walled carbon nanotube bundles, resulting in the formation of hybrid materials. Monolayer protected gold nanoclusters prepared by modified Brust synthesis route were organized on SWNT bundles by cycling-the potential in dichloromethane between -1 to +1 V at a scan rate of 50 mV/s. Monolayer protected nanoclusters in electrolyte solutions possess ionic space charge around them (double layer charging), making them suitable for organization on nanotube bundles, by tuning the electrostatic interactions. More significantly, analysis of the double layer capacitance of these hybrid materials shows almost ten times increase in capacitance compared to that of bare SWNT bundles. We believe that these hybrid materials are potentially useful in nanoelectronics.
Keywords: double layer capacitance; double layer charging; hybrid materials; monolayer protected gold nanoclusters; single-walled carbon nanotubes